2013
DOI: 10.2147/vhrm.s43909
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function testing to predict hyporesponsiveness to clopidogrel in patients with chest pain seen in the emergency department

Abstract: BackgroundA dual antiplatelet regimen has been shown to reduce the risk of major adverse cardiovascular events after percutaneous coronary intervention. However, there is little information available on inhibition of platelet aggregation in patients with a prior coronary stent presenting with chest pain. This study evaluated the prevalence of hyporesponsiveness to clopidogrel and factors associated with this in patients presenting to our emergency department with chest pain who had previously undergone coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…However, although the rate of female patients in the CR+ group was higher than the rate of female patients in the CR-group, no significant relationship was found between CR and gender (Table 1). When the mean age was examined, no significant difference was found between the CR+ and CR-groups in support of previous studies (17,18).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, although the rate of female patients in the CR+ group was higher than the rate of female patients in the CR-group, no significant relationship was found between CR and gender (Table 1). When the mean age was examined, no significant difference was found between the CR+ and CR-groups in support of previous studies (17,18).…”
Section: Discussionsupporting
confidence: 87%
“…Studies have reported higher CR in women (17,18). However, although the rate of female patients in the CR+ group was higher than the rate of female patients in the CR-group, no significant relationship was found between CR and gender (Table 1).…”
Section: Discussionmentioning
confidence: 87%
“…It has previously been reported that high platelet reactivity (HPR) on clopidogrel treatment is more frequent in AA thus increasing the risk of in-stent restenosis and progression of atherosclerotic disease. 15 On the other hand, HPR might also contribute to reduce the bleeding events in AA patients. The rate of bleeding events in AA patients after PCI might therefore be underestimated compared to non-AA who are more likely to respond to clopidogrel.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was a preferential use of clopidogrel in AA. It has previously been reported that high platelet reactivity (HPR) on clopidogrel treatment is more frequent in AA thus increasing the risk of in‐stent restenosis and progression of atherosclerotic disease . On the other hand, HPR might also contribute to reduce the bleeding events in AA patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6] This is clinically significant because HPR is an independent risk factor for 12-month cardiovascular death and nonfatal myocardial infarction (MI).…”
mentioning
confidence: 99%